Critical Professional Praxis in Residence Life. Issue 168 (2nd December 2019) - Kortegast, Carrie; Croom, Natasha N.
Abstract: How can residence life professionals develop communities where social justice is moved from a theoretical perspective to an integrated practice? This chapter provides a case study for residence life staff to use to explore and to guide critical professional praxis in residence halls.